2017
DOI: 10.1021/acs.joc.7b01497
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Oxidative Cyclization of Alkynes with Sulfonylhydrazides Leading to 2-Sulfonated 9H-pyrrolo[1,2-a]indol-9-ones

Abstract: A copper-catalyzed oxidative cyclization procedure has been developed for the production of 2-sulfonated 9H-pyrrolo[1,2-a]indol-9-ones via the direct sulfonylation of N-propargyl-substituted indoles with sulfonylhydrazides and tert-butyl hydroperoxide (TBHP). This novel protocol, which tolerates a broad range of functional groups, offers a simple, efficient, and atom-economical route to a series of fluorazones in good yields under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…The Liang group reported that the cascade of sulfonylation, cyclization, O‐addition, oxidation was able to achieve the construction of 2‐sulfonyl pyrrolo[1,2‐a]indol‐9‐ones (Eq. 28‐1).…”
Section: Sulfonyl Radiacls‐mediated Reactionsmentioning
confidence: 99%
“…The Liang group reported that the cascade of sulfonylation, cyclization, O‐addition, oxidation was able to achieve the construction of 2‐sulfonyl pyrrolo[1,2‐a]indol‐9‐ones (Eq. 28‐1).…”
Section: Sulfonyl Radiacls‐mediated Reactionsmentioning
confidence: 99%
“…In 2017, Liang group disclosed a CuCl 2 . 2H 2 O‐catalyzed tandem reaction of N ‐propargyl‐substituted indoles and sulfonylhydrazides for the synthesis of 2‐sulfonated 9 H ‐pyrrolo[1,2‐a]indol‐9‐ones with an assistance of TBHP (Scheme ) . In this work, the authors found that TBHP were necessary for this reaction.…”
Section: Additive Effect On the Tandem Reactionmentioning
confidence: 93%
“…The formation of 9H- Using the CuCl 2 • 2H 2 O/TBHP/AcOH system, 9Hpyrrolo[1,2-a]indol-9-ones (fluorazones) 468 were obtained from N-propargyl indoles 466 and aryl and hetarylsulfonyl hydrazides 467 (Scheme 205). [256] The synthesis of 1H-pyrrolo[1,2-a]indoles 471 using 2-aryl N-propargyl indoles 469 and aromatic sulfonyl hydrazides 470 under the action of the Cu(NO 3 ) 2 • 3H 2 O/ TBHP/AgTFA system was performed in DCE at 90°C under air. During this transformation, CÀ S, CÀ C, and C=O bonds are constructed and 1,2-migration of the aryl fragment takes place (Scheme 206).…”
Section: Construction Of Five-membered Heterocyclesmentioning
confidence: 99%